2019
DOI: 10.7150/jbji.34452
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment and Outcomes of Calcaneal Osteomyelitis in Adults: A Systematic Review

Abstract: Abstract. Introduction: Calcaneal osteomyelitis is an uncommon and challenging condition. In this systematic review we aim to analyse the outcomes from concomitant use of bone debridement and soft tissue management for patients diagnosed with calcaneal osteomyelitis.Materials & Methods: A complete computerised and comprehensive literature search of Pubmed and Cochrane database was undertaken from January 2000 to October 2018. During the review, studies were screened for information about the surgical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Even a recent study (Waibel et al 2019 ) showed that 50% of the CO patients had to undergo secondary below-knee amputation even if they had already received total calcanectomy. The optimal surgical strategy for CO remains controversial (Sabater-Martos et al 2019 ). We have reported the outcomes of the cortical bone windowing followed by eggshell-like debridement and local vancomycin- and gentamicin-loaded CS for the treatment of patients with type III CO. Our findings can be summarized under the following 4 aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even a recent study (Waibel et al 2019 ) showed that 50% of the CO patients had to undergo secondary below-knee amputation even if they had already received total calcanectomy. The optimal surgical strategy for CO remains controversial (Sabater-Martos et al 2019 ). We have reported the outcomes of the cortical bone windowing followed by eggshell-like debridement and local vancomycin- and gentamicin-loaded CS for the treatment of patients with type III CO. Our findings can be summarized under the following 4 aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The successful treatment of CO with limb salvage remains a challenge, primarily being attributable to the unique anatomical structure and function of the calcaneus, with limited surrounding soft tissue and blood supply. Clinical efficacy remains unsatisfying, with high risks of infection relapse and amputation (Merlet et al 2014 , Sabater-Martos et al 2019 , Waibel et al 2019 ).…”
mentioning
confidence: 99%
“…A study on the surgical outcomes of intraarticular calcaneal fractures found that patients aged >30 years had poor outcomes compared with those under 30 years, thus leading to complication (14). Additionally, age >65 years is an important risk factor of calcaneus osteomyelitis (15). Healthy patients who develop osteomyelitis following a traumatic injury have the highest chance of recovering at young age (8).…”
Section: Discussionmentioning
confidence: 99%
“…18 ) may be a complication of any intervention, and it is usually a clinical diagnosis. Diagnostic imaging and bacteriological analysis are applied to confirm the diagnosis and to find the etiology [ 23 ]. Symptoms most often appear sometime after the procedure.…”
Section: Tendinopathymentioning
confidence: 99%
“…In the early stages, it is challenging to differentiate between infection and postoperative changes on MRI. Osteomyelitis of the calcaneus is seen as bone marrow edema with contrast enhancement [ 23 ]. If an abscess is present, a central fluid collection, destruction of bone and extensive contrast enhancement are visible.…”
Section: Tendinopathymentioning
confidence: 99%